Investigations on morphology and ferroelectric properties of NaNbO 3-PbTiO3 composite ceramics - Prasatkhetragarn A. (2014)
Ceramics in NN-PT system with a formula (1-x)NaNbO3-(x) PbTiO3 (where x=0, 0.1, 0.2,.., 1.0) were prepared by a solid statemixed oxide technique. The phase formation behavior and microstructure were studied using X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The dielectric and ferroelectric properties of the compounds were studied and discussed. Phase pure perovskites of NN-PT ceramics were obtained over a wide compositional range. This work was then aimed to determine the phase formation, morphology, dielectric and ferroelectric properties of NN-PT ceramics. Interestingly, the results showed that the addition of PT have been strongly affected on morphology and ferroelectric properties of NN ceramics. Copyright © Taylor & Francis Group, LLC.